Combining ability for grain yield and other agronomic characters in maize (Zea mays L.) - Banik, BR; Naher, Kamrun; Uddin, M Shalim; Ahmed, S; Rashid, MH (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(1) June 2009 15-18